2019
DOI: 10.1186/s40001-019-0391-8
|View full text |Cite
|
Sign up to set email alerts
|

Cost effectiveness of bilateral risk-reducing mastectomy and salpingo-oophorectomy

Abstract: Background Growing demand for risk-reducing surgery in individuals with inherited susceptibility to cancer leads to the question whether these procedures are cost effective for the executing hospitals. This study compared the clinical costs for bilateral risk-reducing mastectomy (BRRM) with and without different types of reconstruction, risk-reducing salpingo-oophorectomy (RRSO), and their combinations with corresponding reimbursements in the statutory health-care system in Germany. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The reimbursement of prophylactic surgeries for BRCA -mutation carriers does often not cover the costs of executing hospitals in Germany [ 89 ]. There is a potential conflict of interest which may in the worst case impact the care and health benefit of BRCA -mutation carriers if this applies to Switzerland too.…”
Section: Discussionmentioning
confidence: 99%
“…The reimbursement of prophylactic surgeries for BRCA -mutation carriers does often not cover the costs of executing hospitals in Germany [ 89 ]. There is a potential conflict of interest which may in the worst case impact the care and health benefit of BRCA -mutation carriers if this applies to Switzerland too.…”
Section: Discussionmentioning
confidence: 99%
“…For the second group, two surgical events are considered that have the purpose of removing the target organ, breasts, and/or ovaries, called risk-reducing mastectomy (RRM), in its contralateral or bilateral presentation; and risk-reducing bilateral salpingo-oophorectomy (RRBSO) [33,[53][54][55]. Both surgeries are cost-effective for long-term risk management [56][57][58].…”
Section: Effects On Quality Of Life In the Risk Care Of Patients Carr...mentioning
confidence: 99%
“…Risk-reducing surgeries can help prevent diseases and thus preserve health and result in additional life years in good health. Recognizing that these aspects of RRS are the most important, there are also data to suggest that RRS in BRCA-mutation carriers is cost effective compared to potentially avoidable cancer treatment costs [ 93 , 94 ]. Schrauder et al demonstrated that long-term health care costs can be reduced by RRS after genetic testing of BRCA mutation carriers in the German system.…”
Section: Prophylactic Surgerymentioning
confidence: 99%